System for distributed control of melt temperature of polymer in a screw extruder - Mitroshin, V. N. (2017 International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2017)
Modeling problem of polymer melt temperature range in extruder screw was solved as a function of spatiotemporal distribution of extruder cylinder temperature. Structural description of automated process as an object with distributed parameters was obtained. Automatic system of distributed control of polymer melt temperature in a single-screw extruder metering zone was developed. Accuracy of control parameter stabilization is much higher in comparison with the known solutions.